Role and impression management of women lawyers in the home and workplace - Cruz, Ana Carmela B. (2013., 2013)
This study focused on the roles of women in the home and their impression management strategies they do in the workplace. The research objectives were: to analyze the roles of women lawyers in their home and in their workplace, to know the difference of the impressions of women lawyers from their workplace to their families, to understand how the women lawyers balance their roles as mothers and as lawyers, and to differentiate the self-presentation of women lawyers in their family and in their workplace.
The case study method was used to analyze the respondents comprising of lawyers from the Baguio City Justice Hall.
The researcher used the concept of the Looking Glass Self from George Herbert Mead's Symbolic Interactionism, and the concept of Impression Management by Erving Goffman in the Presentation of Self Everyday Life, and the Role Theory.
Results showed that women still maintain traditional/maternal roles in the home. They also participate highly in decision making. It has been found out that there is also lesser patriarchy and is moving into a more democratic home environment.
It was also found out that women lawyers are dominating the workplace, but gender difference does not affect how they practice their profession.
Findings also showed that women lawyers are able to balance their roles by clearly delineating their impression management as mothers and as lawyers. This study showed that women lawyers are successful in fulfilling role demands of their maternal roles and work roles.
Recommendations are to study the counterpart, male lawyers, their roles as fathers and lawyers, and how they fulfill their traditional roles in the family. To further research and analyze the position of mothers in the family and the shifting domination of workplace from male to female, and its effect to the workplace environment; and to study the competition of women in their workplace and how it affects the relationship between them -- Author's abstract.
Thesis (Bachelor of Arts in Communication) -- University of the Philippines Baguio, 2013.
Includes bibliographical references (leaves 97-102).
Keywords: Women lawyers -- Philippines